Odpowiedzi

  • Użytkownik Zadane
2009-10-19T21:37:22+02:00
A) 11 * (-11) + (-12) * (-12) + 13 * (-13) = -121+144-169=-146
b)-7,5 * 20 + (-4) * (-5,5) * (-10) - (-100) * 100 * 3,7=
-150-220+37000=36630
c) 1²₃ * (-9) - 4²₇ * 1,4 + (-3³₅) * (-1¹₉)=(5/3)*(-9/1)-(30/7)*(14/10)-(18/5)*(-10/9)=-15-6+4=-17
d) -(-2⁴₅) * (-³₇) - (-3,6) * (-²₉) - 4,9 * (-³₁₄)=(14/5)*(-3/7)+(36/10)*(-2/9)-(49/10)*(-3/14)=(-42/35)-20+(21/20)=(-168/140)-(2800/140)+(147/140)=-2821/140=-20,15
1 5 1
2009-10-19T21:48:15+02:00
A) 11 * (-11) + (-12) * (-12) + 13 (-13) = -121 + 144 + (-169) = -192
b)-7,5 * 20 + (-4) * (-5,5) * (-10) - (-100) * 100 * 3,7 = -150 + (-220) - (-37000) = -36630
c) 1²₃ * (-9) - 4²₇ * 1,4 + (-3³₅) * (-1¹₉) = 5/3 * (-9/1) - 30/7 * 14/10 + (-18/5) * (-10/9) = -15 - 6 + 6²/₉ = -21 + 6²/₉ = -14⁷/₉
d) -(-2⁴₅) * (-³₇) - (-3,6) * (-²₉) - 4,9 * (-³₁₄) = -(-14/5) * (-3/7) - (-36/10) * (-2/9) - 49/10 * (-3/14) = -1,2 - 36/45 - (-1¹/₂₀) = -2 -(-1¹/₂₀) = -19/20
1 5 1